THE IMPACT OF NON-PERFORMING LOANS AND THE BI RATE ON RETURN ON ASSETS - Yuttama, Faizal Rizky (Jurnal EBI, 2024)
The increase in interest rates also brings changes in the management of funding sources and distribution of funds (credit). Changes in interest rates of course not only affect the profits generated by banks, but also how banks manage the interest income earned and interest paid. This research aims to determine the effect of non-performing loans (NPL) and the Bank Indonesia Interest Rate (BI Rate) on Return on Assets (ROA). The sample used in this research is state-owned banks listed on the Indonesian Stock Exchange (BEI) for the period 2020-2022. The research method used is an associative method with a quantitive approach. The data analysis technique used is multiple linear regression. The research results show that Non Performing Loans (NPL) have a negative and significant influence on Return on Assets (ROA) and the BI Rate has a negative and insignificant influence on Return on Assets (ROA).